Electroanalytical determination of trace chloride in room-temperature ionic liquids. - Villagrán, C; Banks, C; Hardacre, C; Compton, R (2004)
The electroanalytical quantification of chloride in [C4mim][BF4], [C4mim][NTf2], and [C4mim][PF6] ionic liquids has been explored using linear sweep and square wave voltammetry. Cathodic stripping voltammetry at a silver disk electrode is found to be the most sensitive. The methodology is based on first holding the potential of the electrode at +2.0 V (vs Ag wire), to accumulate silver chloride at the electrode. On applying a cathodic scan, a stripping wave is observed corresponding to the reduction of the silver chloride. This stripping protocol was found to detect ppb levels of chloride in [C4mim][BF4], [C4mim][NTf2], and [C4mim][PF6]. Although other methods for chloride have been reported for [BF4](-)- and [PF6](-)-based ionic liquids, no methods have been reported for [NTf2](-) ionic liquids.